JUSTICE A YEARNING IN THE IMPLEMENTATION OF THE CONTRACT IN THE SOCIETY - Siti Malikhatun Badriyah (Diponegoro Law Review, 2017)
The contract is very important in the life of society in the activities of economy, especially since the Foundation in various business activities. The contract is based on the agreement that creates a legal relationship between debtor and creditor. On the other hand often arise out of various problems in the contract, especially concerning the imbalance of legal relationship between the parties. The existence of an imbalance that ultimately gives rise to injustice. Even to this day still be a yearning for Justice, has not realized in various implementation contract in Indonesia